Qualitative and Quantitative Assessment of T2-Weighted Imaging Signal Variations in Prostate MRI Following Different Abstinence Periods: A Study in Young Healthy Men - Ma W; Ren B; Gao Y; Bai W (Journal of Multidisciplinary Healthcare)
Wenjun Ma,1,* Baoming Ren,1,* Yanjun Gao,2 Weixian Bai2 1Department of Urology, XI’an No.3 hospital, The Affiliated Hospital of Northwest University, Xi’an, Shaanxi Province, 710018, People’s Republic of China; 2Department of Medical Imaging, XI’an No.3 hospital, The Affiliated Hospital of Northwest University, Xi’an, Shaanxi Province, 710018, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weixian Bai, Department of Medical Imaging, Xi’an No.3 hospital, The Affiliated Hospital of Northwest University, No. 10 East Section, Fengcheng 3rd Road, Weiyang District, Xi’an, Shaanxi Province, 710018, People’s Republic of China, Tel +86 17749010935, Email bai_weixianbwx@126.comObjective: This study evaluates the impact of an abstinence period on the image quality of high-field prostate magnetic resonance imaging (MRI).Methods: Male patients who underwent prostate MRI at Xi’an No.3 hospital between November 2021 and November 2022 were included in this study. The patients were divided into two groups based on whether they had ejaculated within three days prior to the MRI examination. Two radiologists assessed the boundary sharpness of the peripheral zone (PZ) and central gland (CG) using a double-blind 3-Point Likert scale. Regions of interest (ROIs) were marked bilaterally on the PZ and CG in sagittal T2-weighted images (T2WI). The signal intensity (SI) of the ROIs was measured, and the signal intensity ratio (SIR) was subsequently calculated. The Wilcoxon rank-sum test and independent samples t-test were employed to compare differences between the two groups.Results: A total of 50 young male patients participated in the study, with 20 patients having an abstinence period of more than 3 days and 30 patients having an abstinence period of 3 days or less. Qualitative analysis revealed that the prostate structures were more easily identifiable in the abstinence group compared to the ejaculation group (P ≤ 0.05). Quantitative analysis showed that the SIR of the PZ and CG was lower in the ejaculation group than in the abstinence group (P ≤ 0.05 for both), with a particularly significant difference observed in the peripheral zone.Conclusion: To obtain more accurate results in prostate MRI examinations, it is recommended that patients abstain from sexual activity for at least 3 days prior to the examination.Keywords: image quality, MRI, prostate, T2-weighted imaging